Evaluation of outcome following clamp assisted mini open reduction and internal fixation with intramedullary nailing of subtrochanteric femoral fractures - Prajapati, Chirag G.; Dabhi, Rasik B.; Maru, Nikunj D. (International Journal of Research in Orthopaedics, 2019)
Background: Subtrochanteric fractures of the proximal femur have been defined as the fractures extending from lesser trochanter distally for 5 cm. These fractures usually occur in two age distributions. In the elderly osteopenic population resulting from trivial trauma as fall from standing height or in the younger ones as a result of high energy trauma. Incidence has been on the rise and they comprise about 7 to 10% hip fractures and could lead quickly to large amount of blood loss and other complications. Methods: This is a multicentric prospective prognostic study level 1 consisting of 25 patients admitted in government civil hospital, Ahmedabad during April 2013 to May 2015 having high subtrochanteric femur fractures treated by clamp assisted reduction and intramedullary nailing. Out of these, 20 patients (80%) came for final follow up with average follow up of 11.5 months and evaluated for union, complication and functional outcome. Results: In our study final outcome is assessed based on hip outcome score (modified) based on which 85% had excellent outcome, 10% had good outcome and 5% had fair outcome with none of the patient having poor outcome. Conclusions: We found that clamp-assisted reduction and intramedullary nail fixation provides excellent reduction quality, high rate of fracture union, with no apparent increase in complications in subtrochanteric fractures of the femur.